A New Activity Assay Method for Diamine Oxidase Based on Matrix-Assisted Laser Desorption/Ionization Time-of-Flight Mass Spectrometry - Strnad, Jan; Soural, Miroslav; Šebela, Marek (Molecules (Basel, Switzerland), 2024)
Copper-containing diamine oxidases are ubiquitous enzymes that participate in many important biological processes. These processes include the regulation of cell growth and division, programmed cell death, and responses to environmental stressors. Natural substrates include, for example, putrescine, spermidine, and histamine. Enzymatic activity is typically assayed using spectrophotometric, electrochemical, or fluorometric methods. The aim of this study was to develop a method for measuring activity using matrix-assisted laser desorption/ionization time-of-flight (MALDI-TOF) mass spectrometry based on the intensity ratio of product to product-plus-substrate signals in the reaction mixtures. For this purpose, an enzyme purified to homogeneity from pea (Pisum sativum) seedlings was used. The method employed α-cyano-4-hydroxycinnamic acid as a matrix with the addition of cetrimonium bromide. Product signal intensities with pure compounds were evaluated in the presence of equal substrate amounts to determine intensity correction factors for data processing calculations. The kinetic parameters kcat and Km for the oxidative deamination of selected substrates were determined. These results were compared to parallel measurements using an established spectrophotometric method, which involved a coupled reaction of horseradish peroxidase and guaiacol, and were discussed in the context of data from the literature and the BRENDA database. It was found that the method provides accurate results that are well comparable with parallel spectrophotometry. This method offers advantages such as low sample consumption, rapid serial measurements, and potential applicability in assays where colored substances interfere with spectrophotometry.
Keywords: Pisum sativum; reaction rate; hrách setý; Substrate Specificity; MALDI; spektrometrie hmotnostní - ionizace laserem za účasti matrice; Kinetics; enzyme kinetics; activity assay; substrátová specifita; amine oxidase; polyamine; Spectrometry, Mass, Matrix-Assisted Laser Desorption-Ionization; kinetika; Enzyme Assays; Amine Oxidase (Copper-Containing); enzymatické testy; histaminasa